2018
DOI: 10.3934/dcdss.2018033
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of Cattanneo-Christov heat flux in CNT suspended nanofluid flow over a stretching porous surface with suction and injection

Abstract: The present study analyzes the heat energy transfer in nano fluids flow through the porous stretching surface. Cattanneo-Christov heat flux model is employed to study the heat energy transfer. Darcy law is used to discuss the flow characteristics over the different types of permeable sheets with suction and injection. Nanofluids is considered as water based single-walled carbon nanotubes (SWNTs) and multi-walled carbon nanotubes (MWNTs) nanofluids. A comparative study for SWCNT and MWCNT is also made. Governin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Further, the more recent attractive investigations of various models with CCTM and their effectiveness under the different physical constraint's levels described in the literary works. [7][8][9][10][11][12] Recently, researchers turned their idea towards hybrid types of nanofluids to achieve enhanced heat transfer for realistic applications. Thus, Animasaun et al 13 and Bhatti et al 14 reported the studies for ternary and hybrid nanofluids through horizontal and vertical channel flow situations.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the more recent attractive investigations of various models with CCTM and their effectiveness under the different physical constraint's levels described in the literary works. [7][8][9][10][11][12] Recently, researchers turned their idea towards hybrid types of nanofluids to achieve enhanced heat transfer for realistic applications. Thus, Animasaun et al 13 and Bhatti et al 14 reported the studies for ternary and hybrid nanofluids through horizontal and vertical channel flow situations.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also been conducted on porous plate, porous plate resting on elastic foundations using higher-order shear deformation theory (Arani et al, 2017). Numerical investigation of Cattanneo–Christov heat flux is investigated by (Akbar and Nadeem, 2017; Akbar et al, 2018) in which Carbon Nano Tube (CNT) Suspended Nanofluid and Porous channel saturated with nanofluid and porous surface with section and injection are researched numerically.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 64 removed methyl orange from aqueous solution with the help of Amino-functionalized (NH 2 -MWCNTs) firstly. Akbar et al 65 presented heat energy transfer of nanofluids passing through the permeable stretching sheet. The transfer was done under the effect of Cattaneo-Christov heat flux theory.…”
Section: Introductionmentioning
confidence: 99%